Amnesty International's Challenge in Addressing the Women's Rights Crisis (Gender Apartheid) after the Taliban's Political Coup in Afghanistan - Rio Sundari; Melani Railis Sofyanti; Hussain Yusri Bin Zawawi (WIMAYA, 2026)
After the Taliban coup in Afghanistan, women's rights deteriorated further, creating a state of so-called Gender Apartheid. Violations included restrictions on access to schools and jobs, forced marriages, withholding of identity cards, and bans on public appearances. Many women were imprisoned and tortured for violating religious rules. As evidenced by Amnesty International's report, more than 50% of women in Afghanistan currently experience Gender Apartheid, down from 78% in 2021 and 60% in 2022. This research aims to understand the challenges Amnesty International faces in addressing the women's rights crisis after the coup. The method used is a Qualitative Approach with a Liberal Feminism Perspective and International Organization Theory according to Clive Archer. The results showed that the challenges were divided into internal and external challenges. Internal challenges such as the safety of activists and lack of funding. External challenges include a lack of support from major countries, the complex Taliban culture, and distrust of Amnesty International.